ANALYSIS OF FATIGUE FRACTURE BASED ON PERIDYNAMIC - 石宏顺; 钱松荣; 张国浩; 徐婷; 原群盛 (Jixie qiangdu)
Perdynamic（PD） is used for analyzing crack propagation in engineering material fracture,the bonds constitute to the constitutive relation of the peridynamic,and the broken bonds represent to material fracture,but it can’t be used for the fatigue analysis.Based on the Miner’s linear cumulative damage theory,the bond fatigue break criterion was proposed instead of the old break criterion,the PD fatigue fracture model for high cycle fatigue was constructed.Finally,a bending fatigue fracture analysis was carried out on a standard involute gear,the results show that the fatigue fracture process for gear by PD fatigue fracture model is consistent with experiment,the PD fatigue fracture model provides a method which consists of life prediction and fatigue crack propagation.